Understanding Buerger’s Disease: Symptoms, Diagnosis and Management Strategies - Muciek, Adrianna; Mocarska, Martyna; Orłowska, Anna; Strakowska, Katarzyna; Opalska, Laura; Maryńczak, Anna; Mencel, Jan; Nitschke, Nicole (Quality in Sport, 2024)
Buerger’s disease, also known as thromboangiitis obliterans (TAO), is a rare but serious condition that primarily affects the blood vessels in the limbs. This inflammatory vascular disease is characterised by the formation of blood clots in the small and medium-sized arteries and veins, which results in a reduction in blood flow. Patients typically present with symptoms such as pain in the extremities, ulcers, and in severe cases, gangrene. The disease is most commonly observed in young male smokers, which highlights the strong correlation between tobacco use and the onset of this condition. A comprehensive understanding of Buerger’s disease is essential for prompt diagnosis and effective management. This review will examine the historical context, symptoms, diagnostic criteria, therapeutic approaches, and future directions in research and treatment.